We have that the following two points lie on the line:
• (-2, 0) and (4, 6)
And we need to find the equation of the line that passes through both points.
To find the equation of the line, we can proceed as follows:
1. Apply the two-point equation of the line, which is given by:
![y-y_1=(y_2-y_1)/(x_2-x_1)(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/hkbzvop4iz62zgm93u190774353c4ig6id.png)
2. We have to label both points as follows:
• (-2, 0) ---> x1 = -2, y1 = 0
• (4, 6) ---> x2 = 4, y2 = 6
3. Now, we can substitute the corresponding points into the two-point equation of the line:
![\begin{gathered} y-y_(1)=(y_(2)-y_(1))/(x_(2)-x_(1))(x-x_(1)) \\ \\ y-0=(6-0)/(4-(-2))(x-(-2)) \\ \\ y=(6)/(4+2)(x+2) \\ \\ y=(6)/(6)(x+2) \\ \\ y=x+2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rnk7m3fitd0kry6arv35fxu7ldmt2el7w6.png)
Therefore, we have that the slope of the line is m = 1, and the equation of the line is y = x + 2.
Therefore, in summary, the equation of the line is y = x + 2 (Option D).